Diseño de un sistema solar de calentamiento de agua sanitaria para faenamiento avícola en la ciudad de Catamayo - Yaguana Cañar, Dennis Andrés (2023)
The present research aims to design a Solar Thermal System (STE) focused on the production and storage of hot sanitary water for the slaughtering process of chickens in a poultry farm in the city of Catamayo. It consists of the installation of low temperature by a natural circulation or thermosyphon for applications below 100 °C. Initially, it detailed the most relevant information about solar energy as a renewable source and its use in places with a higher incidence for the application of thermal systems. Also, the classification of the different types of solar collectors and accumulators is according to their operation. The Domestic Hot Water (DHW) energy demand for the slaughterhouse is established through the field and solar resource analysis on the site using PVsyst 7.2 software, in order to use the f (f-chart) calculation method and obtain reliable data on the useful energy used and system performance over an annual period. After that, the appropriate dimensions for the accumulation system, piping, isolation, and calculation of the auxiliary system are determined to provide the remaining energy to fully cover the energy demand necessary to reach the ideal temperature of 60°C for broiler blanching. The entire system design is based on the recommendations established by the Ecuadorian Construction Standard (NEC) and international standards such as IDEA’s technical specifications. Finally, an economic study of the system is presented and the amount of money saved if conventional energy sources are used is evaluated, as well as the payback period of the invested capital if the designed system is put into operation. Keywords: Solar Thermal System (STE), Domestic Hot Water (DHW), Solar radiation, Solar collectors, Thermosiphon, Thermo tank, Poultry blanching.